Application Of Islamic Business Ethics Ms Glow in Maintaning Brand Loyalty and Brand Reputation - Karina Adra Azzahra; Nurul Asfiah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to analyze and explain the influence of Brand Dilution on Brand Reputation, Brand Dilution on Brand Loyalty, Brand Reputation on Brand Loyalty, Brand Dilution on Brand Loyalty with Brand Reputation as mediation. This research is included in the type of explanatory research, using path regression analysis and a quantitative approach. This research was conducted at the MS Glow Clinic Malang with a sample size of 100 people. The sampling technique uses accidental sampling. Data collection was carried out by distributing questionnaires. The data analysis technique uses a range of scales and path analysis with the IBM SPSS version 21 computer program. The application of Islamic Business Ethics such as honesty and social care plays an important role in building brand loyalty by creating trust and a strong emotional connection between brands and consumers. The results of this research show that the Brand Dilution scale is in the very backward category, Brand Loyalty is in the very loyal category and Brand Reputation is in the very good category. Brand Dilution has a positive and significant effect on Brand Reputation, Brand Dilution has a positive and significant effect on Brand Loyalty, Brand Reputation has a positive and significant effect on Brand Loyalty, Brand Reputation cannot mediate Brand Dilution on Brand Loyalty because MS Glow's ability to survive makes consumers see it as a positive thing.